Synthesis, isolation and characterization of thiolate-bridged dinuclear complexes from [(η5-c5h5)m(co)3]2 [m=cr,mo] / Ngue Chin May - Ngue, Chin May (2012)
The reactivity of [CpM(CO)3]2 (M=Cr(1), Mo(3)) together with their congener, [CpM(CO)2]2 (M=Cr(2), Mo(4)) towards aryl disulfide ligands have been studied. The organic ligands include: (i) dicyclohexyl disulfide (ii) thienyl disulfide. Reactions that involve 1 occurred under mild condition via the highly reactive radical CpCr(CO)3•. However, the reaction conditions with 2 and 4 are at elevated temperature. All the products have been characterized spectroscopically and structually via IR, 1H, 13C and 31P NMR, LCMS, elemental analyses, single crystal x-ray diffraction and cyclic voltammetry. Works are summarized below.(i) The reaction of 1 with dicyclohexyl disulfide at 60 ºC for 60 h has led to the isolation of primary product [CpCr(CO)2]2 S (5) followed by a total decarbonylation of [CpCr(SC6H11)]2S (6). After prolonged thermolysis, 6 was fully converted to a cubane-like cluster Cp4Cr4S4 (7). Reaction of 4 with Dicyclohexyl Disulfide at elevated temperature had led to the isolation of a pair of isomeric products trans-syn and trans-anti [CpMo(CO)(SC6H11)]2(8) , [Cp2Mo2(CO)(O)(SC6H11)2] (9) and [Cp3Mo3(CO)4(μ3-O)(SC6H11)] (10) as main products. Thermolytic studies followed by 1H NMR indicated that 8 underwent stepwise decarbonylation and oxidation to afford 9 and 10.(ii) The facile reaction of [CpCr(CO)3]2 (1) with Thienyl Disulfide at ambient temperature had led to the isolation of CpCr(CO)3H (11) as the primary products and [CpCr(CO)2]2S (5) respectively. The reaction involves the 17e radicals CpCr(CO)3· from the facile thermal dissociation of the Cr-Cr bond. At elevated temperature, [CpCr(CO)2]2S (5) and [CpCr(S2C4H3)]2S (12) were isolated as produts. Thermal degradation had led to a total decarbonylation of [CpCr(S2C4H3)]2S (12). Prolong thermolysis of 12 was completely converted to Cp4Cr4S4, as final thermolytic product. The reaction of 4 with one equimolar of Thienyl Disulfide at ambient and elevated temperature had led to a pair of isomeric products, trans-syn ii [CpMo(CO)(C4H3S2)]2 (13a) , trans-anti [CpMo(CO)(C4H3S2)]2 (13b) dan [CpMo(O)(C4H3S2)]2O (14).